The use of tablet computers in the learning and teaching of first level compulsory school pupils with an emphasis on literacy - Þorvaldsdóttir, Jóhanna; Gunnþórsdóttir, Hermína; Engilbertsson, Guðmundur (Menntavísindasvið Háskóla Íslands, 2018)
This article is based on data from a qualitative research project conducted in two Reykjavík primary schools in spring 2014. The research objectives are to gain an understanding of the use of tablet computers in early elementary education, focusing on information, media and technology literacy. Cyberspace and digital media play a constantly growing role in most people’s daily lives and ICT has strongly inf luenced culture and social relations. Many see smartphones and tablet computers as the heralds of a new age and believe their inclusion in schoolwork can enrich education and help teachers to meet students’ diverse needs, as well as signalling the advent of new priorities in learning and teaching. The use of ICT and, in particular, tablet computers in schoolwork has been the subject of considerable discussion which, among other things, has focused on students’ increasingly urgent need for opportunities to use new media at school, since digital communication has become such a prominent part of their lives in general. In modern society, digital communication technology is generally seen as an important aspect of daily life. The widespread use of computers and internet-related innovation has strongly impacted the operation of the school and diverse communication potentialities have engendered new types of literacy, for example digital literacy/computer literacy, media literacy and information literacy. The National Curriculum for the Primary School emphasises the need to support literacy in this wider sense and to regard computers as powerful tools for the creation of multiple contexts. The main objectives of policymakers regarding learning and teaching ref lect the debate outlined above. Technology has, for example, transformed the environment of reading and writing; the concept of literacy has acquired a wider meaning and ICT is now envisioned as an integral part of other subjects, thus benefiting students in general. This new reality calls for an urgent transformation in school operations, and many 21st ...